2022
DOI: 10.1002/qre.3097
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling and availability optimization of condenser used in steam turbine power plants using GA and PSO

Abstract: The prominent objective of the present study is to optimize the availability of condenser units in steam turbine power plants. For this purpose, a novel stochastic model is proposed by considering a condenser as a system consisting of seven subsystems. All the time‐dependent random variables associated with failure rates followed exponential distribution while repair rates are arbitrarily distributed. Furthermore, to attain the optimum value of system availability nature‐inspired algorithm has been applied. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Kumar et al [ 49 ] (2022) used metaheuristic approaches in the optimization of operational availability of cooling towers of STTPs. Saini et al [ 50 , 51 ] optimized the availability of condenser of STTPs, and biological and chemical units of treatment plants using evolutionary and swarm-based algorithms. It is observed that many researchers carried out studies related to the design of sewage treatment plant, but the reliability aspects of plants as well as the power generating unit is not so extensively discussed so far in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kumar et al [ 49 ] (2022) used metaheuristic approaches in the optimization of operational availability of cooling towers of STTPs. Saini et al [ 50 , 51 ] optimized the availability of condenser of STTPs, and biological and chemical units of treatment plants using evolutionary and swarm-based algorithms. It is observed that many researchers carried out studies related to the design of sewage treatment plant, but the reliability aspects of plants as well as the power generating unit is not so extensively discussed so far in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) Parameter setting of the genetic algorithm For the mathematical model constructed for the optimization of the RLG device revenue, the GA can be used to optimize the search for process parameters and maximize the plant revenue while satisfying the constraints. The GA in this section is coded with real numbers and each individual is a string of real numbers [13,26,27]. The results of the device gain prediction in the process of calculating the extremes are used as individual fitness values and are calculated as follows:…”
Section: Genetic Algorithm To Optimize Rlg Device Yieldmentioning
confidence: 99%
“…Similarly, some adaptive techniques proposed in (Alakent, 2020) with adjustable predictor weights are also suggested for online measurements in chemical plants. Genetic algorithms and Particle Swamp Optimization‐based algorithms are proposed in (Saini et al, 2022) to optimize the use of condensers in power plants. These prediction algorithms and their supported knowledge‐based systems are becoming popular in the power system measurement domain for accurately measuring electrical parameters.…”
Section: Detailed Analysis Of Available Literaturementioning
confidence: 99%